2022
DOI: 10.1186/s40246-022-00385-0
|View full text |Cite
|
Sign up to set email alerts
|

Variants in genes related to development of the urinary system are associated with Mayer–Rokitansky–Küster–Hauser syndrome

Abstract: Mayer–Rokitansky–Küster–Hauser (MRKH) syndrome, also known as Müllerian agenesis, is characterized by uterovaginal aplasia in an otherwise phenotypically normal female with a normal 46,XX karyotype. Previous studies have associated sequence variants of PAX8, TBX6, GEN1, WNT4, WNT9B, BMP4, BMP7, HOXA10, EMX2, LHX1, GREB1L, LAMC1, and other genes with MRKH syndrome. The purpose of this study was to identify the novel genetic causes of MRKH syndrome. Ten patients with MRKH syndrome were recruited at Beijing Obste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Following a thorough literature review, the subjects were further screened for the presence of the mutations in the following genes: PAX8, TBX6, GEN1, WNT9B, BMP4, BMP7, HOXA10, GREB1L, LAMC1, TBC1D1, KMT2D, HOXD3, DLG5, HIRA, GATA3, LIFR, CLIP1, SHOX, HNF1B, ITIH5, RBM8A, and NR1B1. (Michael Finkel and Vinod Misra 2023;Williams et al 2017;Gervasini et al 2010;Renard et al 2019;Chu et al 2022;Triantafyllidi et al 2022;Herlin, Petersen, and Brännström 2020;N. Chen et al 2022) Variations were identified in three out of the ten individuals.…”
Section: Specific Vsd Filtering Of Variants and Genetic Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Following a thorough literature review, the subjects were further screened for the presence of the mutations in the following genes: PAX8, TBX6, GEN1, WNT9B, BMP4, BMP7, HOXA10, GREB1L, LAMC1, TBC1D1, KMT2D, HOXD3, DLG5, HIRA, GATA3, LIFR, CLIP1, SHOX, HNF1B, ITIH5, RBM8A, and NR1B1. (Michael Finkel and Vinod Misra 2023;Williams et al 2017;Gervasini et al 2010;Renard et al 2019;Chu et al 2022;Triantafyllidi et al 2022;Herlin, Petersen, and Brännström 2020;N. Chen et al 2022) Variations were identified in three out of the ten individuals.…”
Section: Specific Vsd Filtering Of Variants and Genetic Diagnosismentioning
confidence: 99%
“…TBX6 has previously been associated with MRKH syndrome due to a substantial mutation burden in a Chinese MRKH cohort (Ma et al 2022). The third variant was a heterozygous missense mutation in the DLG5 gene, where a nonsense mutation has previously been implicated as the underlying cause of the patient's MRKH syndrome (Table 3) (Chu et al 2022).…”
Section: Specific Vsd Filtering Of Variants and Genetic Diagnosismentioning
confidence: 99%
“…Optical genome mapping is a newer cytogenomic method with higher resolution for the detection of both imbalanced and balanced structural variation and has recently been applied in a study by Brakta et al (73). In more recent years, whole-exome and wholegenome sequencing analyses have been applied for genome-wide detection of genetic variation at the nucleotide level (74,75,(96)(97)(98)(99)(100)(101)(102)(103)(104)(105). Investigations have included both extended familial cases and larger patient cohorts identifying variants of interesting genes, most notably GREB1L (99, 101, 102) and PAX8 (75).…”
Section: Genetic Research In Mrkh Syndromementioning
confidence: 99%